Structure and Function of the Plant Alternative Oxidase: Its Putative Role in the Oxygen Defence Mechanism. Issue 3 (June 1997) - Wagner, Anneke M.; Moore, Anthony L.
Abstract : Current understanding of the structure and function of the plant alternative oxidase is reviewed. In particular, the role of the oxidase in the protection of tissues against oxidative stress is developed.